The Enemy In The Household Family Violence In Deauteronomy And Beyond - Reeder, Caryn A. (Michigan Baker Academic, 2012)
Three laws in Deuteronomy command violence against a family member--the enemy in the household--who leads others away from covenantal obligations to God. Several biblical and post-biblical narratives make use of such violence. In this fresh approach to
Keywords: Bible. -- Deuteronomy -- Criticism, interpretation, etc. Bibel Bibel -- Deuteronomium